Small states : meeting challenges in the global economy : interim report (Commonwealth Secretariat LondonGB, 1999)
Address the question of what makes small states different. Looks at the various key challenges that small states face. Develops a framework for addressing them, and describes further work the Task Force intends to undertake as it completes its task. Sets out strategies towards small states to be implemented by the World Bank, the Commonwealth Secretariat, the Commission of the European Communities, IMF, UNCTAD and the WTO.
Bibliography: p. 67-68